Młodzież wobec wartości - Anna Błasiak (Jesuit University Ignatianum in Krakow, 2017)
The aim of the article was to show specific knowledge of young people and their world of values, whose original objective is to serve educational work. Adolescence is the time in which the processes of creating individual value system and shaping viewpoint take place. Educational support is essential in this period since despite profound sensitivity to values, discovering values by a young person does not necessarily lead to identification with them. Beside theoretical investigation, the article includes conclusions resulting from the study conducted by the author concerning values adopted and realized by young people. Questions regarding values of the young generation remain up-to-date and significant since they exhibit both social (young people are the future of the society and its chance) and individual character (values influence the shape and quality of man's life).